Computational pathology and ophthalmic medical image analysis : first International Workshop, COMPAY 2018, and 5th International Workshop, OMIA 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16-20, 2018, Proceedings /: first International Workshop, COMPAY 2018, and 5th International Workshop, OMIA 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16-20, 2018, Proceedings. (2018) - Unknown
No abstract available